Pembuatan Website Wisata Pulau Madura - Kenny Jonathan Wijaya; Silvia Rostianingsih (Jurnal Infra, 2017)
Media for promotion is necessary to attract the attention of the public and tourists to come and visit island of Madura, Website is media that can be used to assist the promotion or publication with information that introduces attractions with easy access. This thesis will be made web-based application that utilizes MySQL, jQuery, JavaScript, YouTube iFrame API and the Google API with the programming language used is PHP. As well as making a video using Adobe Premiere Pro CS6 and Adobe After Effects Pro CS6 displayed on the page can be viewed by visitors.In this website, visitors can browse news, events, articles, gallery, destinations, and accommodation. Not only that, visitors can searching for destination through a search bar and a map using Google Map API and use rating and review on destinations. Visitors can also make requests to add destinations, news, events, articles, and accommodation.The test results indicate that the website created using MySQL, jQuery, JavaScript, YouTube iFrame API and the Google Map API can run well in Chrome, Firefox, and Safari browser. Geolocation function with Google Map API that used for map direction and nearest location cannot be used effectively when user use Chrome version 50. The results of questionnaires that obtained from 12 respondents concluded the percentage of overall application, design, navigation, and facilities provided on website with the percentage 25% for 5 points, 58.3% for 4 points, and 16.7% for 3 points with maximum 5 points.